1984
DOI: 10.1007/bf00499297
|View full text |Cite
|
Sign up to set email alerts
|

Molecular charge and electrophoretic mobility in cetacean myoglobins of known sequence

Abstract: Fourteen myoglobins of known sequence were examined by polyacrylamide gel electrophoresis at five pH values. Gels at each pH divided the sequences into six to eight distinct classes, while the combination of the results of three gels at different pH levels distinguished 13 of 14, or 93%, of the sequences. The relative mobility of the myoglobins in the gels is significantly correlated with the charges of the proteins calculated from the pK values of the ionized groups. Major differences in mobility corresponded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…This is because differences in the rate of migration of protein variants are a direct consequence of amino acid substitutions that affect net electrostatic charge (Selander et al 1986). Electrophoretic studies of protein variants of known amino acid sequence have demonstrated that this method detects most nucleotide substitutions resulting in amino acid replacements (Ramshaw et al 1979;McLellan 1984). However, the allelic variation revealed electrophoretically underestimates the total genetic variation at a locus because of silent nucleotide substitutions (Kreitman 1983) and amino acid replacements that do not alter mobility under standard conditions (Coyne 1982).…”
Section: Enzyme Polymorphism and Genetic Variationmentioning
confidence: 97%
“…This is because differences in the rate of migration of protein variants are a direct consequence of amino acid substitutions that affect net electrostatic charge (Selander et al 1986). Electrophoretic studies of protein variants of known amino acid sequence have demonstrated that this method detects most nucleotide substitutions resulting in amino acid replacements (Ramshaw et al 1979;McLellan 1984). However, the allelic variation revealed electrophoretically underestimates the total genetic variation at a locus because of silent nucleotide substitutions (Kreitman 1983) and amino acid replacements that do not alter mobility under standard conditions (Coyne 1982).…”
Section: Enzyme Polymorphism and Genetic Variationmentioning
confidence: 97%
“…The one-dimensional procedure separated all of the myoglobins studied here, but under only one of the five electrophoretic conditions used (McLellan, 1984). Under the other four buffer conditions the five myoglobins resolved into only three or four mobility classes.…”
Section: Discussionmentioning
confidence: 99%
“…The five rnyoglobins (Table I) (McLellan, 1984). The lyophilized protein was dissolved at a concentration of 0.125 mg/rnl in a 9 M urea, 2% Nonidet P-40 detergent, 2% mercaptoethanol, and 2% pH 9-11 arnpholyte (LKB) mixture.…”
Section: Methodsmentioning
confidence: 99%
“…1978). It is possible to have small sequence differences between proteins which result in charge differences at some pH values but not at others (McLellan, 1984). Relative electrophoretic mobility can be maximized near the isoelectric point, where the difference in charge between two proteins will be greatest, as the total charge o f each is small.…”
Section: Discussionmentioning
confidence: 99%